Is Bananaworld nonlocal?. (November 2020) - Stairs, Allen
Abstract: Jeffrey Bub (2018) investigates what we can learn about quantum mechanics from the structure of the correlations it predicts and apart from its detailed mathematical machinery. The present discussion is in the spirit of Bub's project. I examine two arguments, one from Clifton, Pagonis and Pitowsky (1992), and the other from Maudlin (2014). If either is correct, the non-signaling correlations by themselves entail that the quantum world is causally nonlocal. This paper calls both arguments into question. However, it also points out that even if the criticisms succeed, this doesn't settle whether quantum mechanics is causally nonlocal. The answer to that question depends on considerations that go beyond the correlations alone. Arthur Fine's "random devices in harmony" Fine (1981) will play a role as a tool for thinking about correlations that violate Bell-type inequalities. Highlights: The minimalism of Bub's Bananaworld provides a useful device for exploring questions of locality. Reasoning about quantum nonlocality requires careful attention to counterfactual claims Violations of Bell inequalities, by themselves, don't prove action at a distance.